Current and emerging pharmacotherapy for recurrent bacterial vaginosis - Sobel, Jack D; Sobel, Ryan (Expert opinion on pharmacotherapy, 2021)
Given the frequency of recurrent bacterial vaginosis (RBV), enhancing treatment and preventing recurrence have become the central target of pharmacotherapy today. Antimicrobial failure is occurring at a time when knowledge of pathogenesis of bacterial vaginosis (BV) and RBV is incomplete, limiting rational treatment modification. The current manuscript reviews pathogenesis of RBV and the performance of available antimicrobials as well as attempts employed to enhance activity and pharmacologic strategies to reduce BV recurrence and refractory vaginal disease. The authors also provide their expert perspectives on the subject area, including their outlook for the future. In the face of an empty pipeline of new antibiotics, strategies have emerged to enhance existing antibiotic efficacy, which include modifying drug dose, treatment duration, long-term prophylactic regimens, and use of biofilm disrupting agents. It is likely that future effective therapy will include several simultaneous and consecutive treatment components, including combinations of antibiotics, antibiofilm agents, and probiotics. Measures to prevent sexual transmission and reinfection are also essential.